PEMANFAATAN ABU SEKAM PADI DALAM INOVASI PEMUPUKAN KACANG HIJAU (Vigna radiate L) DI LAHAN GAMBUT - Yoyon Riono; Mulono Apriyanto (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2020)
This study aimed to determine the effect of rice husk ash on yield and growth of peanut plants. This research has been carried out in the experimental garden of the Faculty of Agriculture of the Islamic University of Indragiri Tembilahan, Tembilahan Hulu District, Indragiri Hilir Regency. The time of the study began from April to July 2017. This research was a field trial using the Randomized Block Design (RBD) method which consisted of 6 levels of treatment, they are; without rice husk ash, 1 ton/ha of rice husk ash, 2 tons/ha of rice husk ash, 3 tons/ha of rice husk, 4 tons/ha ash rice husk ash, and 5 tons/ha of rice husk ash. Each treatment was repeated three times to obtain 18 trial plots in the field. Data of this study were analyzed using Analysis of Variance (ANOVA). The results showed that the administration of rice husk ash with various treatment doses, had a significant influence on the growth and yield of peanut plants. The treatment that has the best effect on the growth and yield of peanut plants has been found, which is an average of 3 tons/ha and 5 tons/ha.